Economies of Scale Versus Technological Change in the Natural Gas Transmission Industry - Aivazian, Varouj A.; Callen, Jeffrey L.; Chan, M. W. Luke; Mountain, Dean C. (The Review of Economics and Statistics, 1987)
Varouj A. Aivazian, Jeffrey L. Callen, M. W. Luke Chan, Dean C. Mountain, Economies of Scale Versus Technological Change in the Natural Gas Transmission Industry, The Review of Economics and Statistics, Vol. 69, No. 3 (Aug., 1987), pp. 556-561